2022
DOI: 10.1371/journal.pone.0278606
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the barriers and facilitators to accessing and utilising mental health services in regional, rural, and remote Australia: A scoping review protocol

Abstract: Introduction Australians from regional, rural, and remote areas face diverse and complex challenges in accessing and utilising mental health services. Previous research has pointed to a range of individual, community, structural, and systemic barriers at play, however, limited literature has synthesised the knowledge on this topic. Parallel to this, information on the facilitators to accessing and utilising mental health services for this group is not well documented. This protocol describes the methodology to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, access to psychological interventions in prison settings can be challenging. In rural areas of Australia, access to psychological services can be challenging for several reasons [ 43 ]; custodial settings in these areas may face the same issues, including a lack of access to qualified psychological staff. Therefore, it is important to consider interventions that can be delivered by other health and social care professionals.…”
Section: Discussionmentioning
confidence: 99%
“…However, access to psychological interventions in prison settings can be challenging. In rural areas of Australia, access to psychological services can be challenging for several reasons [ 43 ]; custodial settings in these areas may face the same issues, including a lack of access to qualified psychological staff. Therefore, it is important to consider interventions that can be delivered by other health and social care professionals.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 However, accessing appropriate mental health support can be challenging for many people living in rural Australia. 27 Behavioural activation (BA) has been shown effective in improving mood in adults. In a codesigned trial with local partners, we are examining the feasibility and acceptability of implementing a BA teletrial delivered collaboratively with Financial Wellbeing & Capability Programs-Outback SA (FWCP) offered by Centacare Catholic Country SA (CCCSA), a not-for-profit organisation in South Australia.…”
Section: Case Study Example: Increasing Access To Mental Health Servi...mentioning
confidence: 99%
“…There is good evidence that financial stress can result in a low mood 25,26 . However, accessing appropriate mental health support can be challenging for many people living in rural Australia 27 . Behavioural activation (BA) has been shown effective in improving mood in adults.…”
Section: What Might Be the Benefits For Rural Australians In Particip...mentioning
confidence: 99%
“…Poor overall health literacy has been associated with socioeconomic disparities, race, age, gender, and cultural factors (Agner et al., 2023). Some research in Australia has suggested a recognised poor MHL in migrant refugees, aboriginal and islander peoples (Day et al., 2021; Kavanagh et al., 2023). However, MHL from a cultural context has not been well studied (Daluwatta et al., 2022).…”
Section: Background and Significancementioning
confidence: 99%
“…While mental illness rates may not differ by culture, each culture responds differently to mental health challenges (Altweck et al., 2015). MHL has been studied in many diverse populations such as university students in Arabic countries (Almanasef, 2021; Alshehri et al., 2021; Jafari et al., 2021; Mahmoodi et al., 2022; Noroozi et al., 2018), Chinese teachers (Chen et al., 2021), Australian migrant and aboriginal peoples (Day et al., 2021; Kavanagh et al., 2023), and European university students (Marwood & Hearn, 2019; Montagni & González Caballero, 2022). Despite this, many claim that understanding MHL within a cultural context is still in its infancy (Allen et al., 2016; Daluwatta et al., 2022; Park, 2020; Subica, Aitaoto, Link, et al., 2019; Subica, Aitaoto, Sullivan, et al., 2019; Vovou et al., 2021).…”
Section: Background and Significancementioning
confidence: 99%